2022
DOI: 10.3390/agronomy13010059
|View full text |Cite
|
Sign up to set email alerts
|

Key Technologies for an Orchard Variable-Rate Sprayer: Current Status and Future Prospects

Abstract: An orchard variable-rate sprayer applies the appropriate amount of plant protection products only where they are needed based on detection data from advanced sensors, a system that has attracted increasing attention. The latest developments in the detection unit, variable control unit, and signal-processing algorithm of the variable-rate sprayer are discussed. The detection of target position and volume is realized with an ultrasonic sensor, a laser scanning sensor, or other methods. The technology of real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 96 publications
(152 reference statements)
0
12
0
Order By: Relevance
“…3,4 However, the current spraying methods result in most pesticide droplets being intercepted by the soybean surface branches and leaves. 5 This causes uneven deposition of droplets in the soybean canopy, resulting in ineffective control of pests and diseases. Meanwhile, when spraying in the field, fine droplets can easily drift from the target by surrounding airflow.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 However, the current spraying methods result in most pesticide droplets being intercepted by the soybean surface branches and leaves. 5 This causes uneven deposition of droplets in the soybean canopy, resulting in ineffective control of pests and diseases. Meanwhile, when spraying in the field, fine droplets can easily drift from the target by surrounding airflow.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Many researchers have studied air-assisted boom sprayers. 9 However, some results of these studies also showed that when the airflow passes through a dense crop canopy, the kinetic energy is significantly reduced, resulting in uneven deposits of droplets. 10 The droplet deposits in the middle and bottom of the crop canopy require further improvement.…”
Section: Introductionmentioning
confidence: 99%
“…The penetration and deposition of droplets are increased, and the environmental risk due to spray drift phenomenon is reduced 7,8 . Many researchers have studied air‐assisted boom sprayers 9 . However, some results of these studies also showed that when the airflow passes through a dense crop canopy, the kinetic energy is significantly reduced, resulting in uneven deposits of droplets 10 .…”
Section: Introductionmentioning
confidence: 99%
“…The global fruit industry has become the third-largest agricultural planting industry after the grain and vegetable industries. By 2020, the area of orchards in China had reached 1.33×10 7 hm 2 (Zheng et al, 2020;Wei et al, 2023), ranking first in the world. Orchard pest control has long relied on chemical pesticides.…”
Section: Introductionmentioning
confidence: 99%